Characteristics Associated With Health Care Worker Knowledge and Confidence in Elastomeric Half-Mask Respirator Use. Issue 9 (14th September 2022) - Thurman, Paul; Zhuang, Eileen; Chen, Hegang H.; McClain, Caitlin; Sietsema, Margaret; Fernando, Rohan; McDiarmid, Melissa A.; Hines, Stella E.
Abstract : Mastering any task requires correct knowledge to perform the task and be confident in that performance. Having greater confidence than knowledge in donning and doffing an elastomeric half-mask or facepiece respirators (EHMR) may lead to errors resulting in unintentional exposure and failure to recognize any error occurred. Abstract : Objective: This study evaluated health care workers' (HCWs') knowledge and confidence in using elastomeric half-mask respirator (EHMR) attributes known to influence usage. Methods: Health care workers were surveyed regarding their EHMR donning and doffing experience. Respondents were categorized into competency categories based on their scores. Category differences were analyzed using χ 2 and multiple logistic regression. Results: Seventy-two percent showed high levels of EHMR donning and doffing knowledge and confidence (mastery); however, 21% had greater confidence than knowledge (misinformed). Respiratory therapists had greater odds of mastery than other HCWs ( P < 0.05), whereas those working in medical/surgical and pediatric units had greater odds of doubt than other HCWs ( P < 0.01). Conclusions: Although most HCWs show high knowledge and confidence with EHMR use, strategies to confirm respirator use competency may ensure greater HCWs protection.